Cross-Section Evidence for Balanced and Unbalanced Growth - Demery, David; Demery, Lionel (The Review of Economics and Statistics, 1973)
PpTHE terms balanced and unbalanced appear in many and varied contexts within economic theory. One writer has even suggested that it is a cause of much confusion that 'balance' in economic could mean almost anything (Ohlin, 1959, p. 338). This lack of definition has also characterized attempts at statistical verification of the theories. Balanced in the Nurkse (1953) sense arose in the context of development economics and sought to provide some policy conclusions for less developed countries. Solow-Samuelson-Von Neuman balanced is of more theoretical interest and of broader application. Two recent papers (Swamy, 1967 and Yotopoulos, 1970) laboured under the disadvantage of mixing these two quite separate notions of balanced growth. We shall argue that consequently, the evidence already presented sheds little light on the development controversy. This paper examines evidence for balanced and unbalanced theories in the Nurkse-Hirschman sense (Haberler, 1961; Hirschman, 1958; Nurkse, 1953). Nurkse's balanced argument involves two propositions: firstly, the size of the domestic market is maximized only with a balanced of sectors because, by assumption, excess supply is wasted and excess demands are frustrated; secondly, the size of the market is the main determinant of investment in less developed countries. Therefore, Nurkse viewed balance as a means of stimulating growth. Hirschman's version of unbalanced growth, like Nurkse's theory, was concerned primarily with the inducement to invest. Only Hirschman argued that excess demand and supply are necessary in order to make investment decisions obvious. Excess demand induces investment in supplying industries (backward linkage) and excess supply leads to the establishment of using industries (forward linkage). It is clear that Hirschman's theory of unbalanced applies mainly to the intermediate goods sector. A number of studies (including Bhatt, 1965 and Mathur, 1966)) have made considerable ground in providing a synthesis of the theories, usually developing the fact that Nurkse and Hirschman exempt vertical and horizontal sectors, respectively. Consequently there may not arise a problem of policy choice between balanced and unbalanced growth. In the context of this paper, the most important feature of both theories is the implicit exclusion of the effects of international trade. If trade becomes the engine of growth in any less developed country, the theoretical controversy becomes less relevant for development policy. Furthermore, distortions in sectoral rates due to international trade, do not constitute unbalanced in the Hirschman sense. These considerations render difficult any empirical enquiry.